As contribuições da Educação Popular para a inserção curricular da extensão - Freitas, Aline Zorzi Schultheis de (2025)
University extension, as a dialogical interaction between institutions and the community, enables dialogue between different knowledge and knowledge, promoting integral, permanent and omnilateral human formation. This interaction reinforces training beyond formal teaching spaces, focused not only on teaching techniques, but also on the social commitment and insertion of the student in different territories. In this sense, popular education points out ways for extension work that legitimizes popular knowledge, with an emphasis on the shared construction of knowledge and, at the same time, reconnects society and educational institutions. The National Education Plan, in goal 12, strategy 12.7, establishes that Higher Education institutions must guarantee that at least 10% of the curricular credits of undergraduate courses are allocated to the development of programs and extension projects aimed at large areas of social relevance. In this context, the object of the present study is the contributions of popular education to the curricular insertion of extension in undergraduate courses. The research is linked to the Popular Education line of the Postgraduate Program in Education at the Federal University of Paraíba and the Popular Extension Research Group (Extelar). Thus, the guiding problem of the research was: What are the potentialities of popular education as a reference for the processes of curricular insertion of university extension in undergraduate courses at Brazilian higher education institutions and what challenges emerge in this context? The general objective of the research was to analyze the challenges and potential of popular education as a reference for the processes of curricular insertion of extension in undergraduate courses, from the perspective of different social actors. As for the methodology, it is a qualitative research approach, developed through action research. To this end, ten Agoras and an internal workshop were held collaboratively with members of the Brazilian Association of Public Health (Abrasco) and the Popular Extension Research Group (Extelar), with the aim of discussing how to use the assumptions in popular education in the curricular insertion of university extension in undergraduate courses, thus delimiting the principles and guidelines of popular education that can guide this process. In addition to the Agoras and the workshop produced during the action research, the following were also used as an empirical basis for the present study: the bibliographic survey on the theoretical references of the thesis, which guided the entire action research and resulted in the state of knowledge on the topic; four more Agoras produced by Abrasco, in 2022, on the topic studied; and participant observation of popular extension practices in the UFPB health area. As a result of the research, we concluded that, for the curricular insertion of extension to occur from popular education, it is necessary, first and foremost, to critically reflect on which extension will be inserted into the curriculum, recognizing that extension has different intentions. Thus, the extension to be included in the curriculum must constitute useful social work, based on the articulation between teaching and research. This extension has fundamental characteristics, such as: consisting of procedural actions that enable in-depth knowledge of the territories; promote authentic, empathetic and active listening, which results in true dialogue; encourage social participation; offer social support, connecting with the resistance and struggles of the popular classes; provide multidisciplinary and interdisciplinary experiences; and, finally, promote the active, critical, creative and purposeful participation of students. We also identified, during the research, that the main challenges for the materialization of this curricular insertion from the perspective of popular education are: the devaluation of extension in the academic environment; a traditional and fragmented curriculum, focused on disciplinaryization; the pressure for academic productivism; digital information systems that do not consider the dynamic process of extension; the obligation, which can lead, in some cases, to the curricular inclusion of extension due to mere bureaucracy; and the lack of funding, which affects not only extension, but the entire educational system.